2008
DOI: 10.1093/toxsci/kfn180
|View full text |Cite
|
Sign up to set email alerts
|

Knock down of Caenorhabditis elegans cutc-1 Exacerbates the Sensitivity Toward High Levels of Copper

Abstract: Copper, though toxic in excess, is an essential trace element that serves as a cofactor in many critical biological processes such as respiration, iron transport, and oxidative stress protection. To maintain this balance between requirement and toxicity, biological systems have developed intricate systems allowing the preservation of homeostasis while ensuring delivery of copper to the appropriate cellular component. The nematode Caenorhabditis elegans was exploited to assess the effects of copper toxicity at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 21 publications
4
36
0
Order By: Relevance
“…Ctr1 and ATP7 (Ccc2 in Saccharomyces cerevisiae) are known as major Cu importer and exporter, respectively, from fungi to mammals (70). Besides, a bacterial CutC homolog was found to be involved in Cu export (71,72). We found that all Cu-utilizing organisms had ATP7 and almost all (94%) had Ctr1 orthologs, revealing a good correspondence between the occurrence of Cu transporters (both importers and exporters) and Cu utilization (supplemental Table S3).…”
Section: Resultsmentioning
confidence: 73%
“…Ctr1 and ATP7 (Ccc2 in Saccharomyces cerevisiae) are known as major Cu importer and exporter, respectively, from fungi to mammals (70). Besides, a bacterial CutC homolog was found to be involved in Cu export (71,72). We found that all Cu-utilizing organisms had ATP7 and almost all (94%) had Ctr1 orthologs, revealing a good correspondence between the occurrence of Cu transporters (both importers and exporters) and Cu utilization (supplemental Table S3).…”
Section: Resultsmentioning
confidence: 73%
“…Transcriptional responses are nevertheless highly plastic in C. elegans. Some compounds, such as toxic levels of heavy metals (Calafato et al 2008;Swain et al 2004), can reduce C. elegans survival rates; others, for example quercetin, extend life-span (Pietsch et al 2009). Such responses have, moreover, been linked to specific genes and pathways.…”
Section: Transcriptional Reaction Norms and Abiotic Stress Within A Gmentioning
confidence: 99%
“…Previous reports have identified that stress and toxicosis can have a marked effect on egg laying (time to first egg), duration of reproductive period or total offspring number (Calafato et al 2008;Hughes et al 2009;Lagido et al 2009). CC, TC, NC and bio-electrosprayed animals (BES) all developed synchronous production of between 250 and 300 eggs, a value that is in agreement with the published literature.…”
Section: Genomic Genetic and Reproductive Effects Of Bio-electrospramentioning
confidence: 99%